Resilience and depression in high school students Metropolitan Lima with or without participating in violent acts - Velásquez C., Carlos (2009)
A correlational study was conducted between resilience and depression in educational institutions of Lima, with male and female students from 3rd-5fth secondary, the which a party not involved in violence and other self. The instruments used for assessment were the Resilience Scale and Adolescent Depression Inventory. Results show that positive correlations exist on internal components of both tests, while the correlation between them the relationship is more diverse. We identified differences between violent and nonviolent students. as to the confidence, authoritarianism and suicidal thoughts factors. Also, in comparison intersex, identified differences between women and men regarding the degree of emotional control, decision making, self-criticism, tendency to weep, and other variables. The place of students residence also mark some differences in components of resilience and depression instruments.